2021
DOI: 10.7454/jki.v24i2.864
|View full text |Cite
|
Sign up to set email alerts
|

The Smoking Behavior of Health Workers in Asia: A Literature Review

Abstract: Health workers are role models in preventing smoking behavior, yet many are smokers themselves. This study reviews and analyzes the smoking behavior of health workers in Asian countries, based on databases such as PubMed, EBSCO, and Google Scholar in 2013–2018. It is shown that the prevalence of smoking amongst health workers was 4.6–44%, with the nursing profession showing a higher level than other health professions and with a higher ratio of male to female smokers. Health workers are aware of the dangers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Meanwhile, the prevalence of smoking among female health workers in Indonesia, Nepal, and Syria tends to have a lower prevalence (<5%) and is highest in Armenia and Pakistan (<15%) ( 30 ). These results align with research in Asia which found that the smoking behavior of male health workers is higher than that of female health workers ( 31 ).…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the prevalence of smoking among female health workers in Indonesia, Nepal, and Syria tends to have a lower prevalence (<5%) and is highest in Armenia and Pakistan (<15%) ( 30 ). These results align with research in Asia which found that the smoking behavior of male health workers is higher than that of female health workers ( 31 ).…”
Section: Discussionsupporting
confidence: 90%
“…Smoking among healthcare professionals (HCPs) is a serious issue for occupational health and for health promotion. Although healthcare workers are aware of the dangers of smoking 1 , smoking is not uncommon among them. However, their intervention is critical in promoting healthy behavior and preventing smoking.…”
Section: Introductionmentioning
confidence: 99%